PENGAWASAN PEREDARAN SUPLEMEN MAKANAN OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN DI KOTA PEKANBARU - Rina Wati; Ernawaty " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Observation Of Circulation of Suplemen Food by BBPOM ( Big Hall of Supervisor Medicinize and Food) Pekanbaru. Observation of circulation of food suplemen of vital importance to be conducted. Especially to danger generated by product of suplemen food which is improper used again, have or kadaluarsa of suplemen the food do not have permit circulate, and contain proven dangerous materials endanger consumer soul and health wearing product of suplemen food. As for phenomenon at this research is the lack of observation of BBPOM to circulation of food suplemen without permit to protect society effect of usage of food suplemen without permit. This research method is to have the character of descriptive qualitative, using technique of purposive sampling representing an technique intake of sampel with a[n consideration which is expert in its area. As for becoming informan lock in this research is inspection area and investigation and shares of serlik Big Hall of Supervisor Medicinize and Food Town of Pekanbaru. And becoming complement informan is society as consumer and perpetrator .This research is conducted with interview and observation.From result of research conducted by researcher at Big Hall of Supervisor Medicinize and Food about circulation of food suplemen in the reality conducted observation still less executed as its his. As for used as by theory concept indicator is according to M.Manullang, namely cover: Specifying standard, conducting action assessment, and conduct action correction. Whereas factors influencing observation cover: observation intensity, observation system.Keyword: Observation, specifying standard, assessment action, corrective action